2017
DOI: 10.1371/journal.pone.0172922
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-assisted differentiation of porcine adipose tissue-derived stem cells into glucose-responsive insulin-secreting clusters

Abstract: The unique advantage of easy access and abundance make the adipose-derived stem cells (ADSCs) a promising system of multipotent cells for transplantation and regenerative medicine. Among the available sources, porcine ADSCs (pADSCs) deserve especial attention due to the close resemblance of human and porcine physiology, as well as for the upcoming availability of humanized porcine models. Here, we report on the isolation and conversion of pADSCs into glucose-responsive insulin-secreting cells. We used the stro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 61 publications
(69 reference statements)
1
9
0
Order By: Relevance
“…In agreement, Liu et al (37) mentioned that in case of treatment with MSCs, β-cells insulin immunoreactions were obviously improved and referred the previous findings to the multipotency of MSCs and their abililty to transdifferentiate into insulin producing β cells.…”
Section: Discussionsupporting
confidence: 60%
“…In agreement, Liu et al (37) mentioned that in case of treatment with MSCs, β-cells insulin immunoreactions were obviously improved and referred the previous findings to the multipotency of MSCs and their abililty to transdifferentiate into insulin producing β cells.…”
Section: Discussionsupporting
confidence: 60%
“…Currently, it has been reported that pASCs can transdifferentiate into hepatocytes, 17,24 neurons, 11,25 and pancreatic islet-like clusters. 26 Using lentivirals carrying reprogramming factors, pASCs have also been reprogrammed into induced pluripotent stem cells (iPSCs). 19,27 Song et al also described that pASCs could also differentiate into oocyte-like cells.…”
Section: Multilineage Differentiation Abilitiesmentioning
confidence: 99%
“…For example, 3D printed cell-laden hydrogel scaffolds could not only provide precise spatial distribution of the transplanted cells 241 , but also allow co-printing with immune regulatory cells or agents 242 , enabling highly localized immunregulation. Biomaterials and microprinting technologies can further assist in improving stem cellderived beta cell differentiation and pseudo islet formation 243,244 . The transition from cadaveric islet sources, with unpredictable HLA profiles, to a defined stem cell-derived beta cell source, with the capacity to generate HLA-typed cell banks, provides the opportunity to decrease allogeneic beta cell rejection by tailoring the donor MHC to the patient.…”
Section: Future Directions and Challengesmentioning
confidence: 99%